Secagem do lúpulo (Humulus Lupulus L.): modelagem, cinética e estudo da qualidade do óleo essencial - Ayala, Mariana Bianchi Fazolo (2024)
Hops are of great importance in the beer production process, as their essential oil provides aroma and flavor. Brazil is the third largest beer producer in the world, but it imports almost 100% of the hops used. After harvesting, hops have around 75-80 % moisture in the plant, however, to be used in the manufacture of beer, hops must contain low moisture levels between 8-10 %, making an initial drying stage necessary. With the growing increase in Brazilian domestic demand for hop cultivation and the importance of drying hops for beer manufacturing, a better assessment of the drying of hop cones is necessary. Thus, the objective was to carry out the drying process of hop cones (Humulus lupulus L.), obtaining their drying curve with adjustments to the mathematical models, in addition to evaluating the extraction yield of the essential oil and volatile components. For the drying process, 10 g of the fresh plant, of the Comet variety, were used. Drying was carried out in a forced ventilation oven, at temperatures of 40 ºC, 50 ºC and 60 ºC. Nine mathematical models adjusted by non-linear regression to experimental data were evaluated. The initial humidity of the fresh hops was 79.07 % ± 0.72 % and the total drying times until reaching equilibrium were 10.5 h, 9 h and 7 h for temperatures of 40 ºC, 50 ºC and 60 ºC, respectively. Hop drying curves and drying rates were obtained, showing that internal water diffusion is the predominant phenomenon in the process of drying and removing water from hops. The mathematical models, which best fit the data with satisfactory analytical parameters, for temperatures 40 ºC, 50 ºC and 60 ºC, were the Midilli, modified Midilli, Page and Henderson and Pabis models. The Midilli and Modified Midilli models were the most appropriate to describe the hop drying process for all temperatures studied. To analyze the oil yield, 420 g and 440 g of fresh hops were used, drying in duplicate at temperatures of 40 ºC and 60 ºC, until humidity levels of 8 % and 12 %. A 22 factorial experimental design was carried out, without a central point, using temperature and humidity as factors, with the essential oil content as a response. The best temperature and humidity conditions obtained for the highest content of extracted essential oil were 40 ºC at 12 % humidity and 60 ºC at 8 % humidity. To analyze the volatile components of the essential oil from these extractions, the GC/FID technique was used. The results obtained in the chromatography analysis indicate that there is no significant variation in the composition of the oils obtained under different extraction conditions, presenting the data with signals at similar retention times with the percentage of each component nearby.